Sazonalidade, epidemiologia molecular e virulência do Vírus Sincicial Respiratório (VSR): uma perspectiva dentro do programa brasileiro de vigilância da influenza - Vianna, Lucas Alves (2021)
Respiratory Syncytial Virus (RSV) is the main cause of pediatric morbidity and mortality. The complex evolution of RSV creates a need for worldwide surveillance, which may assist in the understanding of multiple viral aspects. This study aimed to investigate RSV features under the Brazilian Influenza Surveillance Program, evaluating the role of viral load and genetic diversity in disease severity and the influence of climatic factors in viral seasonality. We have investigated the prevalence of RSV in children up to 3 years old with severe acute respiratory infection (SARI) in the Espirito Santo State (ES), Brazil, from 2016 to 2018. RT-qPCR allowed for viral detection and viral load quantification, to evaluate association with clinical features and mapping of local viral seasonality. Gene G sequencing and phylogenetic reconstruction demonstrated local genetic diversity. Of 632 evaluated cases, 56% were caused by RSV, with both subtypes A and B co-circulating throughout the years. A discrete inverse association between average temperature and viral circulation was observed. No correlation between viral load and disease severity was observed, but children infected with RSV-A presented higher clinical severity score (CSS) median, stayed longer in the hospital, required intensive care and ventilatory support more frequently than those infected by RSV-B. Regarding RSV diversity, some local genetic groups were observed in the main genotypes circulation RSV-A ON1 and RSV-B BA, with strains showing modifications in the G gene amino acid chain. Local RSV studies using the Brazilian Influenza Surveillance Program are relevant to assess the suitability and viability of a single network for the surveillance of other respiratory viruses. Understanding seasonality, virulence and genetic diversity can support the suitability of future antiviral drugs and vaccines and assist in the administration of prophylactic strategies.